Parenté hippocratique et parenté aristotélicienne. Quelques réflexions sur les théories biologiques de la Grèce ancienne - Olivier Roux (Pallas, 2009)
Pondering, as regards ancient Greece, the history of the sciences of life and reproduction, one is soon confronted with two contradictory and mutually exclusive discourses: on the one hand the hippocratic theory which accords to woman a role nearly equal to man’s, and on the other hand the system set up by Aristotle and a few others which confines the feminine role to that of a receptacle, denying it the existence of any feminine seed. Now ethnologists and anthropologists of extraeuropean areas have for long stressed the importance of those theories for a global understanding of social bonds and notably those of parenthood. As regards classical antiquity, that theoretical confrontation could then be read as a marker of diversity in the systems of parenthood in the Greek world, but also of an evolution and transformation of certain social relationships in keeping with the development of the City-State.